Institusionalisasi Ilmu dan Krisis Otoritas Keilmuan di Era Digital: Perspektif Sejarah Sosial Pendidikan Islam - Shaleh, Moh. Badrus; Padil, Moh.; Zuhroh, Ni'matuz (Lembaga Yasin AlSys, 2026)
The digital era has transformed the transmission of Islamic knowledge through open platforms and social media. This condition expands the reach of da’wah, but at the same time creates a crisis of scholarly authority in Islamic education. This study aims to analyze the process of knowledge institutionalization in the history of Islamic education and to explain the factors that cause the fragility of scholarly authority in the algorithmic era. This study used a qualitative approach with a library research design through historical and sociological perspectives. Data were obtained from classical and contemporary literature, then analyzed using critical discourse analysis. The results showed three main findings. First, the institutionalization of knowledge in Islam has been related from the outset to power relations, as reflected in the emergence of the madrasah. Second, the current crisis of scholarly authority is caused by an epistemological shift from the scarcity of knowledge to the abundance of information, in which algorithms replace sanad as a mechanism of legitimacy. Third, the reconstruction of scholarly authority requires innovations in the form of digital sanad, algorithmic critical literacy, and interactive virtual halaqah. These findings contribute to the development of Islamic education through a critical framework that connects classical scholarly institutions with digital disruption. The conclusion of this study emphasizes the importance of reconstructing Islamic scholarly authority that is adaptive to the algorithmic era without neglecting the principles of tradition-based scholarly legitimacy. Further studies are recommended to conduct field research on online religious learning communities.